Data from: Seasonal shifts in the insect gut microbiome are concurrent with changes in cold tolerance and immunity - Ferguson, Laura V.; Dhakal, Pranav; Lebenzon, Jacqueline E.; Heinrichs, David E.; Bucking, Carol; Sinclair, Brent J. (Dryad, 2019)
1. Seasonal changes in the environment, such as varying temperature, have
the potential to change the functional relationship between ectothermic
animals, such as insects, and their microbiomes. Our objectives were to
determine: a) whether seasonal changes in temperature shift the
composition of the insect gut microbiome, and b) if changes in the
microbiome are concomitant with changes in the physiology of the host,
including the immune system and response to cold. 2. We exposed laboratory
populations of the spring field cricket, Gryllus veletis (Orthoptera:
Gryllidae), to simulated overwintering winter and spring, we extracted and
sequenced 16S bacterial genomic DNA from cricket guts, to capture seasonal
variation in the composition of the microbiome. 3. The composition of the
gut microbiome was similar between microcosms, and overall me, where
overwintering resulted in permanent changes to these microbial
communities. In particular, the abundance of Pseudomonas spp. decreased,
and that of Wolbachia spp. increased, during overwintering. 4. Concurrent
with overwintering changes in the gut microbiome, G. veletis acquire
freeze-tolerance and immune function shifts temporarily, returning to
summer levels of activity in the spring. Specifically, haemocyte
concentrations increase but survival of fungal infection decreases in the
winter, whereas the ability to clear bacteria from the haemolymph remains
unchanged. 5. Overall, we demonstrate that the gut microbiome does shift
seasonally, and in concert with other physiological changes. We
hypothesize that these changes may be linked, and suggest that it will
next be important to determine if these changes in the microbiome
contribute to host overwintering success.
Seasonal changes in protein content of cricket haemolymph.csv file of
cricket haemolymph protein concentration corresponding with summer, winter
and spring.ferguson dryad cricket protein.csvCricket
melanisationMelanisation values (grey values) of nylon filament implanted
in Gryllus veletis cricketsferguson dryad cricket melanisation.csvferguson
dryad cricket fungusSurvival data for Gryllus veletis infected with
Metarhizium anisopliae in summer, winter, or springferguson dryad cricket
hemocytesHaemocyte concentrations for Gryllus veletis in summer, winter
and springqPCR result for Wolbachia and PseudomonasqPCR results for
Wolbachia and Pseudomonas spp. in the gut of Gryllus veletis crickets over
seasonsferguson ryad final microbiome qPCR.xlsxMH420599-MH421834Sequence
files for microbiomics data
Keywords: cricket; Symbiosis; cold; Gryllus veletis